IDENTIFIKASI BONUS DEMOGRAFI KOTA SOLOK TAHUN 2019 - Syaifullah Urrahman; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aims to determine the demographic identification in 2019 about the age of the population according to age and gender with the population pyramid, determine the dependency rate by determining the age of the population not yet productive, productive age, and non productive age. 1)Population structure according to age and sex, 2)To calculate the dependency rate of villages in the city of solok. This type of research quantitative aprroach. The data source in this study is secondary data obtained population and civil registry office of solok city. The results of this are study. 1)Population structure according to age and sex of the village is determined by the population pyramid, 2)To calculate the dependency rate in the city of solok by determining the age of unproductive, productive age and unproductive age. Keyword : Population structure according to age and gender and dependency figures